The Effect of Transfer Pricing, Profitability, and Capital Intensity on Tax Avoidance (Empirical Study of Property and Real Estate Companies on the Indonesia Stock Exchange In 2020-2023 - Wahyuni, Putu Eka Sri; Nursiam, Nursiam (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to examine the effect of transfer pricing, profitability, and capital intensity on tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Tax avoidance refers to strategies used by companies to reduce their tax liabilities through legal means, while transfer pricing involves setting prices for transactions between related entities to allocate income across different jurisdictions. Capital intensity refers to the amount of capital invested in assets relative to the company's total assets. Profitability is measured by the company's ability to generate earnings relative to its revenue or assets. The sample consisted of 51 companies, selected using purposive sampling, with 21 outliers removed based on predetermined criteria. Data was analyzed using classical assumption testing, followed by hypothesis testing with multiple regression analysis (F-test, t-test, and coefficient of determination) using SPSS version 25. The results show that transfer pricing and capital intensity do not have a significant impact on tax avoidance, while profitability significantly influences tax avoidance. These findings suggest that more profitable companies may engage in higher levels of tax avoidance, possibly due to greater opportunities or incentives to minimize tax payments. The study highlights the importance of profitability as a key determinant in tax avoidance strategies in the property and real estate sector.